Personal Data Protection Policy during Covid-19 Pandemic Era - Moh. Indra Bangsawan; Budi Santoso; M. Junaidi; Dewi Kusuma Diarti; Sandya Mahendra; Engine Kubota (Universitas Muhammadiyah Surakarta, 2023)
Advances in technology and information demand that the law can accommodate all forms of need for legal protection in the future. Objective : This research aims to describe the picture of threats to data resources in the midst of the COVID-19 pandemic as well as describe personal data protection policies in the midst of the Covid-19 pandemic. Methods : This research uses the literature review method. The literary materials obtained are in the form of scientific papers, online media, books, etc. that concerns the analyzed object. Findings : The current personal data protection policy is still based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which until now is considered not optimal to ensure legal protection of data resources in the era of the Covid-19 pandemic. 19. Data reports from the National Cyber and Crypto Agency show that until 2020 cyber attacks in Indonesia have increased to reach 190 million cyber attacks. Function : This research provides an explanation of the urgency of the need for legislation that specifically regulates the protection of personal data. Novelty : There has not been any researches that study the same topic as that discussed in this article.